Impact of diabetes mellitus on the long-term prognosis of patients with hepatocellular carcinoma after hepatectomy. (4th May 2022) - Shen, Guo-Liang; Lu, Yi; Liang, Lei; Lu, Wen-Feng; Diao, Yong-Kang; Xiao, Zun-Qiang; Zhang, Kang-Jun; Zhang, Jun-Gang; Zhang, Cheng-Wu; Liu, Junwei
ABSTRACT: Background: The impact of diabetes mellitus (DM) on the survival of patients with hepatocellular carcinoma (HCC) is still unclear. The present study aims to draw a firm conclusion in terms of evaluating the impact of DM on the prognosis of HCC after hepatectomy. Methods: The pattern of recurrence for HCC was often stratified into early-stage (<2 years) and late-stage (≥2 years) recurrence. Because the early-stage recurrence was mainly attributed to aggressive tumor pathological characteristics, patients who recurrence or die within 2 years were excluded. Cumulative overall survival (OS) and recurrence-free survival (RFS) were determined by the method of Kaplan–Meier, and the independent risk factors of OS/RFS were determined by Cox regression analysis. Results: A total of 426 patients were eventually included. The 3- and 5-year OS in patients with and without DM was 83.7%, 55.1%; and 90.9%, 77.4%, respectively. Multivariate analysis showed that DM was an independent risk factor for OS (HR 1.166, 95% CI 1.056–2.036, P = 0.022) and RFS (HR 1.365, 95% CI 1.043–1.787, P = 0.023). Conclusion: DM is an independent risk factor for long-term prognosis in patients with HCC. Patients with DM after hepatectomy for HCC, thus, need to actively control DM and closer follow-up.